Konstruksi Modal Manusia dan Performa Kualitas Hidup Anak Jalanan (Studi Kasus Lembaga Pemberdayaan Anak Jalanan Griya Baca Malang) - Anugrawati, Luky Kharlina (Jurnal Ilmu Ekonomi dan Pembangunan, 2014)
The purpose of this study were 1) To know the Institute of Street Children Empowerment Griya Baca  efforts in conducting the establishment of human capital in order to improve the quality of life for street children guidance, 2) To find out the extent to which Institute of Street Children Empowerment Griya Baca  do human capital establishment in order to improve the quality of life for street children guidance, 3) To know the aspects that affect the Institute of Street Children Empowerment Griya Baca  in conducting human capital establishment in order to improve the quality of life for street children guidance. The research method is non-probability sampling technique with the method of purposive sampling and accidental sampling. The results are: (1) Institute of Street Children Empowerment Griya Baca efforts in making the establishment of human capital focuses on the empowerment of street children through learning (education and skills) are described in the activities: (a) Coaching routine twice a week (academic and non academic, (b) Outbound street children, (c) music highlights, (d) Creative World Street Children (e) Ramadhan On The Street (f) The skills to make a variety of parcel and trinkets of beads. (2) Aspects that affect the Institute of Street Children Empowerment Griya Baca in conducting human capital establishment include: (a) socialization to parents, society and street children themselves, (b) the limited facilities and infrastructure, (c) environment that supports the child to remain on the streets. Keywords: Street children, human capital, quality of life.JEL Classification: J24, Z13,